The shape of spins - Englert, Christoph; Gonçalves, Dorival; Nail, Graeme; Spannowsky, Michael (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
After the discovery of a Higgs-like particle at the LHC, the determination of its spin quantum numbers across different channels will be the next step in arriving at a more precise understanding of the new state and its role in electroweak symmetry breaking. Event shape observables have been shown to provide extremely sensitive observables for the discrimination of the scalar Higgs boson’s CP quantum numbers as a consequence of the different radiation patterns of Higgs production via gluon fusion vs weak boson fusion in the pp→X+2j selection. We show that a similar strategy serves to constrain the spin quantum numbers of the discovered particle as a function of the involved couplings. We also discuss the prospects of applying a similar strategy to future discoveries of Higgs-like particles.